Evidence for Electron Transfer between Graphene and Non‐Covalently Bound π‐Systems. Issue 29 (17th April 2020) - Brülls, Steffen M.; Cantatore, Valentina; Wang, Zhenping; Tam, Pui Lam; Malmberg, Per; Stubbe, Jessica; Sarkar, Biprajit; Panas, Itai; Mårtensson, Jerker; Eigler, Siegfried
Abstract: Hybridizing graphene and molecules possess a high potential for developing materials for new applications. However, new methods to characterize such hybrids must be developed. Herein, the wet‐chemical non‐covalent functionalization of graphene with cationic π‐systems is presented and the interaction between graphene and the molecules is characterized in detail. A series of tricationic benzimidazolium salts with various steric demand and counterions was synthesized, characterized and used for the fabrication of graphene hybrids. Subsequently, the doping effects were studied. The molecules are adsorbed onto graphene and studied by Raman spectroscopy, XPS as well as ToF‐SIMS. The charged π‐systems show a p‐doping effect on the underlying graphene. Consequently, the tricationic molecules are reduced through a partial electron transfer process from graphene, a process which is accompanied by the loss of counterions. DFT calculations support this hypothesis and the strong p‐doping could be confirmed in fabricated monolayer graphene/hybrid FET devices. The results are the basis to develop sensor applications, which are based on analyte/molecule interactions and effects on doping. Abstract : Organic star‐shaped tricationic molecules interact with graphene and a one‐electron transfer from graphene to the molecules leads to strong p‐doping.